Avaliação da resposta muscular eletromiográfica antes e após o restabelecimento da dimensão vertical em pacientes desdentados totais - Pereira, Ana Aline Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The edentulous patients have as a consequence a relative loss of their masticatory capacity. It is well known that the maintenance of the masticatory function is especially important in edentulous patients, mainly due to the limitations found in rehabilitations by total dentures. The decrease of vertical occlusion dimension may compromise aesthetics and cause morphological and functional alterations such as hypoactivity of masticatory muscles and reduction of masticatory strength. Electromyography involves the detection and recording of electrical potentials of muscle fibers, making it possible to evaluate the function of the muscle in activity and integrity of this system. Therefore, this present work has as general objective to make a comparative analysis of the strength and electrical activity of the masticatory muscles; the superficial masseter layer and the anterior temporal of three edentulous patients with reduced vertical dimension, and who were subsequently subjected to prosthetic rehabilitation treatment. For electromyographic recording, the six-channel EMG-800C (EMG System do Brasil Ltda) electromyograph was used, previously calibrated. Four input channels were used with active electrodes with 20 times amplification gain. At the same time, the masticatory strength was evaluated through a force transducer, linked to the system. All participants of this study were evaluated clinically and electromyographically before and after (about 30 to 60 days) the manufacturing of dentures under parameters of mandibular rest and maximum voluntary mandibular contraction. It was observed an increase of the Masseter and Temporal muscles activity (bilateral), in the two conditions of muscular activity, suggesting an increase in motor tone and increment of new motor units, after the installation of the prosthesis, thus improving the pattern of muscle activity followed by restoration of the appropriate ...(Complete abstract eletronic access below)

Os pacientes edêntulos têm como consequência uma perda relativa da sua capacidade mastigatória. É sabido que a manutenção da função mastigatória tem importância especial nos desdentados, principalmente devido às limitações encontradas nas reabilitações por próteses totais. A diminuição da dimensão vertical de oclusão pode comprometer a estética e causar alterações morfológicas e funcionais tais como hipoatividade dos músculos mastigatórios e diminuição da força mastigatória. A eletromiografia envolve a detecção e o registro de potenciais elétricos de fibras musculares, possibilitando a avaliação da função do músculo em atividade e da integridade desse sistema. Sendo assim, este estudo teve como objetivo fazer uma análise comparativa da força e da atividade elétrica dos músculos mastigatórios; masseter superficial e temporal anterior de 3 pacientes desdentados totais que apresentaram dimensão vertical diminuída, e que foram posteriormente submetidos a tratamento reabilitador protético. Para o registro eletromiográfico, foi utilizado o eletromiógrafo modelo EMG-800C (EMG System do Brasil Ltda) de seis canais, previamente calibrado. Foram utilizados quatro canais de entrada com eletrodos ativos com ganho de amplificação de 20 vezes Concomitantemente foi avaliada a força mastigatória através de transdutor de força, acoplado ao sistema. Todos os participantes deste trabalho foram avaliados clinicamente e eletromiograficamente antes e após (tempo estimado de 30 a 60 dias) a confecção de próteses totais nas condições de repouso mandibular e contração máxima voluntária. Observou-se aumento da atividade (bilateral) dos músculos Masseter e Temporal, nas duas condições de atividade muscular, sugerindo aumento do tônus motor e incremento de novas unidades motoras, após a instalação das próteses, melhorando assim o padrão da atividade ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Prótese total; Eletromiografia; Músculos mastigatórios